Dionizy Królikowski (1862-1836) - wielkopolski dziennikarz, literat i tłumacz - Gzella, Grażyna (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Dionizy Królikowski (1862-1936), a Poznań journalist and writer, was the editor of many newspapers and magazines published on the Polish territories under Prussian rule, in Silesia and Galicia. Knowing Slavic languages and relations prevailing in individual countries, he translated and disseminated works of authors from these countries. He published his own works in periodicals and monographs.